A genome-wide collection of barcoded single-gene deletion mutants in Salmonella enterica serovar Typhimurium. - Steffen Porwollik; Weiping Chu; Prerak T Desai; Michael McClelland (PLoS ONE, 2024)
Genetic screening of pools of mutants can reveal genetic determinants involved in complex biological interactions, processes, and systems. We previously constructed two single-gene deletion resources for Salmonella enterica serovar Typhimurium 14028s in which kanamycin (KanR) and chloramphenicol (CamR) cassettes were used to replace non-essential genes. We have now used lambda-red recombination to convert the antibiotic cassettes in these resources into a tetracycline-resistant (TetR) version where each mutant contains a different 21-base barcode flanked by Illumina Read1 and Read2 primer sequences. A motility assay of a pool of the entire library, followed by a single-tube processing of the bacterial pellet, PCR, and sequencing, was used to verify the performance of the barcoded TetR collection. The new resource is useful for experiments with defined subsets of barcoded mutant strains where biological bottlenecks preclude high numbers of founder bacteria, such as in animal infections. The TetR version of the library will also facilitate the construction of triple mutants by transduction. The resource of 6197 mutants covering 3490 genes is deposited at Biological and Emerging Infections Resources (beiresources.org).